2003
DOI: 10.1295/polymj.35.757
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Reaction of Two Kinds of Molecular-Weight Controlled Biodegradable Polymers

Abstract: ABSTRACT:Poly(ε-caprolactone) (PCL) having controlled molecular weight was synthesized by ring opening polymerization of ε-caprolactone (CL) initiated by ethanol with stannous(II) octanoate or scandium(III) trifluoromethane sulfonate as a catalyst. The hydroxyl end group of the resulting polymer was converted to trimethylsiloxyl group by using hexamethyldisilazane. On the other hand, poly(vinyloxy-t-butyldimethylsilane) (PVOTBDMS) was obtained by aldoltype of group transfer polymerization. Under the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The hydroxyl end group was converted into a trimethylsiloxyl group by using hexamethyldisilazane. [21] Hexamethyldisilazane was used to mask the hydroxyl group at the terminal of the PHO chain. In the 1 H NMR spectrum shown in Figure 5, the terminal methylene proton (CH 2 OH) signal at 4.0 ppm decreased with the passage of time and a new methylene signal at 4.1 ppm, assignable to CHOSi(CH 3 ) 3 , appeared, indicating that the hydroxyl end group of PHO can easily react.…”
Section: Preparation Of Pho Oligomersmentioning
confidence: 99%
“…The hydroxyl end group was converted into a trimethylsiloxyl group by using hexamethyldisilazane. [21] Hexamethyldisilazane was used to mask the hydroxyl group at the terminal of the PHO chain. In the 1 H NMR spectrum shown in Figure 5, the terminal methylene proton (CH 2 OH) signal at 4.0 ppm decreased with the passage of time and a new methylene signal at 4.1 ppm, assignable to CHOSi(CH 3 ) 3 , appeared, indicating that the hydroxyl end group of PHO can easily react.…”
Section: Preparation Of Pho Oligomersmentioning
confidence: 99%
“…[22][23][24] Known from other common catalysts, the activity of metal triflates would not be restrained by moisture and air. Moller et al, 25 Zhou et al, 26 and Nomura et al 27,28 reported the ROP of CL using scandium triflate [Sc(OTf) 3 ] as catalyst preparing LPCLs with controlled molar mass and very narrow molar mass distribution at room temperature. However, there is no reference concerning the preparation of SPCLs with metal triflates.…”
Section: Introductionmentioning
confidence: 99%
“…10 In our previous work, 11 we have succeeded in synthesis of Poly("-caprolactone)-blockPoly{vinyloxy(tert-butyl)dimethylsilaneg, (PCL-b-PVOTBDMS), through a coupling method. Each block unit could be prepared by ring-opening polymerization (ROP) of CL and aldol-type group-transfer polymerization (Aldol-GTP) of VOTBDMS, respectively.…”
mentioning
confidence: 99%